Abstracts of theses and dissertations on Philippine mass communication, 1974-1980 - De Jesus, Emilinda Villanueva (1982)
This study attempts to compile an abstract-bibliography of theses and dissertations on Philippine mass communication submitted to selected academic institutions from 1974 to 1980.